Patterns of treatment for childhood malaria among caregivers and health care providers in Turbo, Colombia (2012)
ABSTRACT: Malaria represents a major cause of death among children in many areas of the world, especially in tropical countries. Colombia constitutes a malaria endemic country in 90% of its territory. This study, undertaken in Turbo (Antioquia), examined care-seeking patterns and barriers to appropriate treatment for Colombian children with fever and /or convulsions, two key symptoms of malaria. The study focused on community perceptions of and responses to febrile illness, using illness narratives as the primary data collection vehicle. The researcher used semi-structured interviews for health narratives with caregivers and health providers. Analyses of 67 illness narratives collected in the course of the study indicated that caregivers, the majority of which are mothers, recognize fever and treat it promptly. They identified fever, chills, headache, vomiting, and weakness as the most frequent symptoms of malaria. Synchronic and diachronic analyses showed that most treatments begin at home. Common home treatments include baths with herbs and use of anti-pyretic drugs. Neither caregivers nor traditional healers conceptualized malaria as a disease that involves the spirits. Caregivers described an intricate mixture of biomedicine, home treatment, and traditional medicine. This pluralistic approach helps to explain, in part, the caregiver’s decision-making process. Moreover, from the biomedical perspective, this complex mixture of knowledge can lead to inadequate treatment of children with malaria.